Biosynthesis and Bioactivity of Prodiginine Analogs in Marine Bacteria, Pseudoalteromonas: A Mini Review - Sakai-Kawada, Francis E.; Ip, Courtney G.; Hagiwara, Kehau A.; Awaya, Jonathan D. (Frontiers in Microbiology, 2019)
The Prodiginine family consists of primarily red-pigmented tripyrrole secondary metabolites that were first characterized in the Gram-negative bacterial species Serratia marcescens and demonstrates a wide array of biological activities and applications. Derivatives of prodiginine have since been characterized in the marine γ-proteobacterium, Pseudoalteromonas. Although biosynthetic gene clusters involved in prodiginine synthesis display homology among genera, there is an evident structural difference in the resulting metabolites. This review will summarize prodiginine biosynthesis, bioactivity, and gene regulation in Pseudoalteromonas in comparison to the previously characterized species of Serratia, discuss the ecological contributions of Pseudoalteromonas in the marine microbiome and their eukaryotic hosts, and consider the importance of modern functional genomics and classic DNA manipulation to understand the overall prodiginine biosynthesis pathway.